Discovering the socio-economic migrant performance on illegal logging activities for deforestation problem solving in Banyuasin Regency, South Sumatera (case study of Sungai Buring traditional village) - Adriani, Dessy; Purbiyanti, Erni; Huanza, M.; Damayanthy, Dini (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2023)
It is often excluded from the handling of illegal logging and deforestation is the release of the socio-economic aspects in problem solving deforestation and forestry development. The purpose of this study was to: 1. Identify the socio-economic characteristics of the migrant who become illegal loggers, 2. Analyze the amount of illegal loggers' income and its allocation to the consumption, and 3. Develop a strategy to overcome illegal logging and forest deforestation based on the socio-economic characteristics of the logger. The analysis showed that socio-economic conditions of the migrant who become illegal loggers illustrates that they are still a low level of education and have productive age. Income earned Rp 4,301,211.00/year/family, lower than the income of Rp 33,070,945.00/year/family after migrating. Income get from illegal logging are Rp 13.087.945/year/family. Average migrant allocates 60.81 % of its total income for consumption, and the remaining 39.19 % is allocated to farming and non-farming activities. This study suggests that there should be an increase in revenue breakthrough in the area of origin to be able to suppress the migration process becomes illegal loggers to other areas. Low income is the core problem of farmers to migrate. Required two basic designs: (1) social engineering with community and (2) technical engineering in the direction of the multiproduct and multifunctional forest benefits to overcome the problems of forestry in the long run.